Alternative fuels – Effects on clinker process and properties. (September 2019) - Chatterjee, Anjan; Sui, Tongbo
Abstract: Use of alternative fuels in cement production has three important perspectives: dimension of the industry, its environmental impacts, and the fitness of the process for the purpose of waste management. The global production volume of cement is >4 billion tonnes for the last five years, the energy consumption was about 11 EJ in 2016, and the annual CO2 emission was 2.2 Gt. External to the industry, there is a huge problem of managing waste, which was at a level of about 2 billion tonnes in 2016. All these parameters will enormously aggravate by 2050, affecting sustainability and climate. Co-processing of certain combustible waste in cement kilns has evolved as an important tool for addressing the problems. The paper primarily deals with the sources and types of waste on one hand and effects on clinker process and properties on the other.